Prospective primary mathematics teachers’ attitude towards statistics - Dahlan, Taufiqulloh; Lumbantoruan, Jitu Halomoan (Universitas Islam Negeri (UIN) Mataram, 2024)
[English]: This study aimed to assess attitudes of prospective primary mathematics teachers (PPTs) toward statistics and how these attitudes are influenced by gender. It adopted Attitudes Towards Statistics Survey (SATS-36) and involved 455 PPTs from 9 Teachers Training Institutions (TTI). Exploratory factor analysis (EFA) was performed because the model fit for confirmatory factor analysis (CFA) failed to yield good indices of reliability and validity. The validated model only contains 27 items in four factors that assess attitudes including competence, values, difficulties, and interests. The prospective teachers’ attitudes toward statistics and the impact of gender were then evaluated using a modified four-factor model. The finding shows that PPTs have a positive attitude toward statistics. In specific, the female participants tend to have a more positive attitude toward statistics than the male. [Bahasa]: Penelitian ini bertujuan menilai sikap calon guru matematika sekolah dasar terhadap statistika dan bagaimana sikap tersebut dipengaruhi oleh jenis kelamin. Penelitian ini mengadopsi Survei Sikap terhadap Statistik (SATS-36) dan melibatkan 455 calon guru dari 9 Lembaga Pendidik Tenaga Kependidikan. Analisis faktor eksploratori (EFA) dilakukan karena model yang cocok untuk analisis faktor konfirmatori (CFA) gagal menghasilkan indeks yang baik untuk reliabilitas dan validitas. Model yang telah divalidasi hanya memuat 27 item dalam empat faktor untuk menilai sikap yang meliputi kompetensi, nilai, kesulitan, dan minat. Sikap calon guru terhadap statistik dan dampak gender kemudian dievaluasi menggunakan model empat faktor yang dimodifikasi. Hasil penelitian menunjukkan bahwa calon guru mempunyai sikap positif terhadap statistik. Secara spesifik, calon guru perempuan lebih mempunyai sikap positif terhadap statistik daripada calon guru laki-laki.